HERAKLEİTOS: KOSMOS'TAN İNSAN'A - Hakan Poyraz (Felsefe Dünyası)
Likewise other Ionian philosophers, Herakleitos was also concerned with the first principle that constitutes cosmos. Man seems to be the subject-matter of his philosophy. While the first principle is fire, the law is logos... Cosmos can be known by logos. The fact, for him, that cosmos is identical with logos and, indeed, since we take part from it, leads to the view that conceiving the universe pass through a true apprehension of man. Furthermore, since logos is the law of the universe, it is also the law of value. By pointin out that "I searched out for myself, Herakleitos contends he has gained the law of the universe by taking himself as the starting point. The Herakleiton expression that "I search out for myself could be a constituent of human philosophy and brings about a conception of human being who has the general and universal truth in his particularity. Accordingly, the goal of this paper will be an evaluation of such a methaphisical treatise from which the idea of the unity of man with the universe can be derived.